PI controller based genetic algorithm for PV inverter using SPWM technique / Muhammad Hafiz Dzikri Mohammad Salihhuddin - Mohammad Salihhuddin, Muhammad Hafiz Dzikri (2025)
This study focuses on optimizing a three-phase photovoltaic (PV) inverter system using Sinusoidal Pulse Width Modulation (SPWM) with Genetic Algorithm (GA)-optimized Proportional-Integral (PI) controllers. PV systems convert DC power from solar panels into AC power compatible with the grid. SPWM plays a critical role in generating smooth AC waveforms essential for grid synchronization. However, traditional PI controllers have limitations in dynamic response and robustness under varying conditions. To address these challenges, GA is utilized to optimize PI controller parameters, aiming to improve inverter efficiency, stability, and response. MATLAB/Simulink simulations are conducted to validate this approach, demonstrating the superior performance of GA-optimized PI controllers in tasks such as setpoint tracking, disturbance rejection, and ensuring system stability. This research seeks to enhance the reliability and efficiency of PV inverters through innovative control strategies, thereby contributing to improved energy conversion and grid reliability. Future initiatives may include experimental validation in real-world PV systems to further refine and validate these control strategies.